A STUDY AMONG ENGLISH TEACHERS’ PERCEPTIONS: INVESTIGATING THE ROLES OF ICT IN INDONESIAN EFL CLASSROOM - Khoirunnisa Isnani (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
The status of English as a foreign language in Indonesia makes the students use this language rarely. Whereas, English as international language and also a compulsory subject in secondary school to university level in Indonesia encourage students to master English. ICT comes with many advantages created innovation in teaching and learning English. Then, the teachers as the key role in the course should utilize it. However, the teachers should know the roles of ICT in teaching English. Therefore, this research aims to analyze English teachers’ perceptions on the roles of ICT in EFL classroom. This descriptive qualitative research involved five English teachers from different schools in Yogyakarta, Indonesia. The research data were gathered using interview. The findings of the research showed that ICT plays role as a tool, a source, and an encouragement of students’ English learning.